(untitled) (The Agriculturists, 2014)
The experiment was conducted at the experimental field of Entomology Division, BARI, Gazipur during Rabi 2007-08. Two microbial insecticides HaNPV @ 0.4ml/L and Bt @ 2g/L along with their combination were tested against H. armigera. The lowest fruit infestation, both in number and weight, was obtained from treatment HaNPV and Bt alternate spraying (11.78%, 9.64%), followed by Bt (13.25%, 10.85%) and HaNPV (17.67%, 13.11%). The highest fruit yield (16.92 t/ha) was obtained from HaNPV and Bt alternate spraying plots followed by Bt (16.65 t/ha) and HaNPV (14.73 t/ha). In case of MBCR, the highest MBCR was obtained from HaNPV and Bt alternate spraying (5.30) followed by HaNPV (4.46) and Bt (3.37). DOI: http://dx.doi.org/10.3329/agric.v12i1.19583 The Agriculturists 2014; 12(1) 68-74